KARAKTERISTIK BAKTERI PEREDUKSI MERKURI (Escherichia coli) DIISOLASI DARI PERAIRAN PANTAI TELUK MANADO - Ijong, Frans G; Dien, Henny A (Sam Ratulangi University, 2011)
ABSTRACTIn the environment like seawater, mercury can be oxidized by some bacteria, such as Thiobacillus, to produce Hg ions which are soluble in water and toxic to marine organisms, such as bacteria, algae, and so on. On the other hand, the occurrence of Pseudomonas, as E. coli, is believed can reduce the number of Hg ions in the environment. An experiment was conducted to count total coliform and total E. coli, to isolate, to identify E. coli isolated from Manado Bay seawater, and to determine the ability of E. coli isolates to do reduction and or oxidation of mercury ions. Seawater samples were collected from the reclamation area, especially close to Tondano River, Sario River and Bahu River around Manado Bay. As a control, some water samples were taken from Bunaken Island waters at Liang and Muka Kampung area. An amount of 500 ml water samples was taken from the sampling site and placed into container, then brought to the laboratory for further analysis, such as total coliform, total E. coli. In addition, some biochemical tests were also carried out in order to identify the isolate. The results showed that nearly all isolates of E. coli (83.3%) exhibited their ability in mercury ions oxidation, while the isolates that can reduce ion mercury were 13.3% only. The highest Hg-ions reduction was influenced by the characteristic of isolates, and mercury ions oxidation was also dependent upon the strain type.Keywords: E. coli, reduction-oxidation, Hg-ions.ABSTRAKDalam lingkungan perairan laut, merkuri dapat teroksidasi oleh bebera-pa bakteri, seperti Thiobacillus. Bakteri ini dapat menghasilkan ion Hg yang la-rut dalam air dan bersifat racun bagi organisme laut lainnya. Di sisi lain, keha-diran Pseudomonas seperti juga E. coli, diyakini dapat mengurangi jumlah ion Hg di lingkungan. Tujuan penelitian ini adalah menghitung total coliform dan to-tal E. coli, untuk mengisolasi dan mengidentifikasinya dari perairan Teluk Manado, dan menentukan kemampuan isolat E. coli dalam mereduksi dan mengoksidasi ion-ion merkuri. Sampel air laut dikumpulkan dari areal reklama-si, terutama di daerah yang dekat dengan Sungai Tondano, Sungai Sario dan Sungai Bahu. Sebagai kontrol, beberapa sampel air (@ 500 sampel ml) diambil dari perairan Pulau Bunaken di Liang dan Kampung Muka, kemudian dibawa ke laboratorium untuk dianalisis lebih lanjut, seperti total coliform, jumlah E. coli. Selain itu, beberapa tes biokimia juga dilakukan untuk mengidentifikasi isolat. Hasil penelitian menunjukkan bahwa hampir semua isolat E. coli (83,3%) menunjukkan kemampuan mereka dalam mengoksidasi ion merkuri, sedangkan isolat yang dapat mengurangi ion merkuri hanya 13,3% saja. Penurunan ion Hg tertinggi dipengaruhi oleh karakteristik isolat, demikian pula dengan kemampuan oksidasi ion merkuti tergantung pada jenis strainnya.Kata kunci: E. coli, reduksi-oksidasi Hg, ion Hg.